2021
DOI: 10.3390/ijerph18041516
|View full text |Cite
|
Sign up to set email alerts
|

Potential Ecological and Human Health Risks of Heavy Metals in Soils in Selected Copper Mining Areas—A Case Study: The Bor Area

Abstract: Surface soil samples were collected near the Open Pit Bor (S1) and Open Pit Cerovo (S2), a grassland along the Borska Reka River (S3) and an unpolluted garden near Slatina village (reference site). Spontaneous plants (dandelion, nettle, coltsfoot, and creeping buttercup) and vegetables (onion, garlic, carrot, parsley, celery, potatoes, dill, and sorrel) were obtained from the former three sites and the reference site, respectively. The samples were analyzed for Zn, Cu, Fe, Mn, and Pb via FAAS. Pollution indice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…The results of the present study are supported by many studies around the world that report that irrigation with water contaminated with heavy metals and metalloids increases the mobile fraction of these contaminants in the soil ( Marrugo-Negrete et al, 2017 , Xiao et al, 2017 , Keshavarzi and Kumar, 2019 , Kumar et al, 2019 ; Adimalla et al, 2020; Filimon et al, 2021 ). The mean concentrations of Cu, Zn and As recorded in the study area were similar to the concentrations reported by Xiao et al (2017) for agricultural soils with mining influence.…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study are supported by many studies around the world that report that irrigation with water contaminated with heavy metals and metalloids increases the mobile fraction of these contaminants in the soil ( Marrugo-Negrete et al, 2017 , Xiao et al, 2017 , Keshavarzi and Kumar, 2019 , Kumar et al, 2019 ; Adimalla et al, 2020; Filimon et al, 2021 ). The mean concentrations of Cu, Zn and As recorded in the study area were similar to the concentrations reported by Xiao et al (2017) for agricultural soils with mining influence.…”
Section: Discussionsupporting
confidence: 87%
“…The concentration of Cu ranged between 2.64 and 13.42 mg/kg dw with a mean value of 6.25 mg/kg dw. Filimon et al (2021) reported a Cu concentration of 3.94 mg/kg dw in onions collected from a copper mining area in Eastern Serbia. The concentration of Mn in onion in the present study (20.15 mg/kg dw) is very much higher than reported in Romania (0.33-4.07 mg/kg dw) (Manea et al, 2020), Ghana (0.07-0.015 mg/kg dw) (Ametepey et al, 2018); Eastern Serbia (9.96 mg/kg dw) (Filimon et al, 2021), and Nigeria (4.26 mg/kg dw) (Muhammad et al, 2021).…”
Section: Levels Of Heavy Metals In Coriander Onion and Tomatomentioning
confidence: 99%
“…Filimon et al (2021) reported a Cu concentration of 3.94 mg/kg dw in onions collected from a copper mining area in Eastern Serbia. The concentration of Mn in onion in the present study (20.15 mg/kg dw) is very much higher than reported in Romania (0.33-4.07 mg/kg dw) (Manea et al, 2020), Ghana (0.07-0.015 mg/kg dw) (Ametepey et al, 2018); Eastern Serbia (9.96 mg/kg dw) (Filimon et al, 2021), and Nigeria (4.26 mg/kg dw) (Muhammad et al, 2021). The range of Zn concentration in the present study was close to the results (11.4-25.5 mg/kg dw) obtained by Amin et al (2013).…”
Section: Levels Of Heavy Metals In Coriander Onion and Tomatomentioning
confidence: 99%
“…Thus, the study of heavy metal pollution in soils is the need of the hour. Many studies have been conducted to explore the spatial distribution of heavy metal pollution in roadside soils [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%